To solve the quadratic equation \((5x + 6)^2 + 24 = 33\), we can follow these steps:
-
Isolate the squared term: \[ (5x + 6)^2 + 24 - 24 = 33 - 24 \] Simplifying this gives: \[ (5x + 6)^2 = 9 \]
-
Take the square root of both sides: \[ 5x + 6 = \pm 3 \]
This results in two separate equations to solve:
- \(5x + 6 = 3\)
- \(5x + 6 = -3\)
-
Solve each equation:
-
For the first equation \(5x + 6 = 3\): \[ 5x = 3 - 6 \] \[ 5x = -3 \] \[ x = -\frac{3}{5} \]
-
For the second equation \(5x + 6 = -3\): \[ 5x = -3 - 6 \] \[ 5x = -9 \] \[ x = -\frac{9}{5} \]
-
-
Final solutions: The values of \(x\) that solve the equation are: \[ x = -\frac{3}{5} \quad \text{and} \quad x = -\frac{9}{5} \]